Expression of β-catenin and AXIN2 in ameloblastomas - Wei, Zhenhui; Zhong, Ming; Guo, Yan; Wang, Yan; Ren, Meisi; Wang, Zhaoyuan (Contemporary Oncology/Współczesna Onkologia, 2013)
Aim of the study: To investigate the expression status and association of β-catenin and AXIN2 in ameloblastoma. Material and methods : 30 ameloblastoma specimens and 10 normal oral mucosa tissues were enrolled in the study. The protein and RNA levels of β-catenin and AXIN2 were detected by immunohistochemistry staining, Western blot, and real-time PCR analysis. The relationship between β-catenin and AXIN2 protein and clinico-pathological parameters and prognosis was subsequently determined. Results: The results show that β-catenin mRNA expression was 1.24-fold higher in ameloblastomas than that in normal mucosa tissues, but AXIN2 mRNA expression was 0.47-fold lower in ameloblastomas than that in normal mucosa tissues (p < 0.05). The Western blot results show that β-catenin and AXIN2 protein in ameloblastomas had a significantly higher level than normal mucosa tissues (p < 0.05). Immunohistochemical staining of β-catenin and AXIN2 protein in ameloblastoma was expressed at a higher level than normal oral mucosa (p < 0.05). Conclusions : AXIN2 and β-catenin play an important role in the tumorigenesis and progression of ameloblastoma.